The Potential Hazards of Human Activity around the Nuclear Plant Site: Case Study of Nuclear Plant Site at Indonesia - June Mellawati (IJRDO-Journal of Applied Science, 2019)
Studies of human activities around nuclear reactor installations that can trigger disasters have been carried out. This is related to BATAN’s plan to develop nuclear facilities in Serpong, Banten. The aim of the research is to identify activities from stationary sources that have the potential to disrupt the safety of nuclear reactors and can trigger hazards such as releasing radioactive material into the environment. The methodology includes the collection of primary and secondary data from human activities around the prospective site, identification and mapping of these sources, screening with the Screening Distance Value (SDV) method. The results showed that until now there had been no chemical industry and oil refineries found around the study area, but there were 10 closest refueling activities within 3.0 - 4.14 km, and 2 gas filling activities within 1.94 - 12.66 km. The results of screening and mapping indicate that the location of the nuclear reactor is in the SDV refueling and gas area so that it needs detailed evaluation using ALOHA software simulation. After detailed evaluation, there is no threat of explosion and fire hazards that need to be worried about nuclear reactor installations, so that they can be categorized as safe. This data is in accordance with the requirements of the International Atomic Energy Agency and the Indonesian Nuclear Energy Regulatory Agency.